ANALISA DAYA TARIKINVESTASI INDONESIA DIANTARA NEGARA TETANGGA ASEAN - Nasir, Mohamad (Badan kebijakan Fiskal, 2010)
Indonesia as an emerging country needs investment's role to increase economic growth, especially after economic crisis in 1998, because government's financing capacity is very limited, so do private sectors. During 1990-2009, value of investment in Indonesia reached a significant growth, DDl grew 24.17% and FDI grew 30.39% per annum. Indeed, these numbers were great numbers. However, role ofDDI and FDI to Indonesian economic were small if we look at ratios of DDl and FDI to GDP that were around 0.65% and 2.29% per annum.Actually, Indonesia has a potential source to attract investors, especially foreign investors to invest in Indonesia. However, Indonesia has a lower competiveness of investment than neighbor countries. There are some reasons that support this statement. First of all, Indonesia has a higher risk of investment. For example, Indonesian political risk score in medium and long term is 5 (high risk), while Singapore, Malaysia, and Thailand have score 1, 2, and 3 respectively. Secondly, based on GC1, Indonesia is in 54th position, whereas Singapore, Malaysia and Thailand are in 3rd, 24th and 36th position respectively. Lastly, Indonesian tax rate (28%) is still higher than Singapore (18%), Vietnam (25%) and Malaysia (25%). Regarding tax rate thoeritically tax rate is a main reason of investors to invest in particularly country. However World Economic Forum (2009) reported that tax rate is not a main problem if an entity will do business in Indonesia. Tax rate in Indonesia was just a 13rd factor of consideration for taking investment decision.The main problems are bureacracy, infrastructure, policy instability, and corruption. In conclusion, Indonesiaan competitiveness for investment is under neighbor countries especially Singapore, Malaysia, Thailand, and Vietname.